Sociological beginnings : the first Conference of the German Society for Sociology - Adair-Toteff, Christopher (Studies in social and political thought, 2005)
This is a translated edition of five of the nine papers and the responses presented at the first conference of the Deutsche Gesellschaft für Soziologie (DGS) that was held in 1910. These are seminal contributions by some of the founders of classical German sociology and social theory, including Max Weber, Georg Simmel, Ferdinand Tönnies, Ernst Troeltsch and Werner Sombart. A substantial introduction discusses the lives and works of the five thinkers, placing them in the context of Germany in the early twentieth century and discussing their personal and societal connections.